Ten Candidate Genes Were Identified to Be Associated with the Great Growth Differentiation in the Three-Way Cross Hybrid Abalone - Qizhen Xiao; Shihai Gong; Zekun Huang; Wenzhu Peng; Zhaofang Han; Yang Gan; Yawei Shen; Weiwei You; Caihuan Ke; Xuan Luo (Animals)
Abalone is an economically important mollusk, whose slow growth has impeded the recovery of its wild populations and development of aquaculture. The three-way cross hybrid abalone ((Haliotis discus hannai♀ × H. fulgens♂)♀ × H. gigantea♂, DF × SS) demonstrated notable diversity in growth traits across the population with genetic differentiation, offering a model for exploring the molecular mechanisms of abalone growth. In this study, a total of 89 SNPs and 97 candidate genes were identified to be associated with growth-related traits of abalone using whole-genome resequencing and a genome-wide association study (GWAS) analysis. Then, ten overlap genes were found among these candidate genes by combining the results of GWAS and comparative transcriptomic analyses between the large individuals (L group) and small individuals (S group) of DF × SS. These overlap genes include up-regulated genes (fabG) and down-regulated genes (HMCN1, TLR3, ITIH3) between the L and the S groups, which are thought to function in growth in other organisms. The biological functions of these candidate genes in abalone still have to be confirmed, but they have improved our understanding of the molecular mechanisms behind abalone growth traits and provided molecular markers for abalone breeding programs.